KAMINALJUYU CHRONOLOGY AND CERAMIC ANALYSIS: AN ALTERNATIVE VIEW. Issue 2 (14th December 2017) - Love, Michael
Abstract : Recently, Inomata and colleagues (2014) proposed a revision to Shook and Popenoe de Hatch's (1999) chronology of Kaminaljuyu, recommending a new chronology based on detailed Bayesian analysis of the calibrated dates. In this article, I present data suggesting that Inomata and colleagues' proposed chronology should be viewed with caution, especially with regard to the apogee of Kaminaljuyu, the Verbena and Arenal phases. Furthermore, the impact of their revised chronology is overstated because the model of highland-to-lowland diffusion that they attack has long been moribund. Abstract : Recientemente, Inomata y sus colegas (2014) plantean una revisión de la cronología de Kaminaljuyu, Guatemala publicada por Shook y Popenoe de Hatch (1999). Ellos proponen una nueva cronología basada en el análisis Bayesiano de fechas calibradas. Los datos aquí presentados sugieren que la cronología de Inomata y colaboradores debe ser considerada con cautela, especialmente en lo que respecta al apogeo de Kaminaljuyu (fases Verbena y Arenal). Asimismo, los impactos que se derivan de dicha cronología revisada son sobreestimados, porque el modelo de difusión de tierras altas a tierras bajas que los autores discuten ha estado en decadencia desde hace muchos años.